Adhesive joints for composite materials produced by additive manufacturing. (November 2019) - Casas Pulido, A F; Bohórquez, O; González-Estrada, O A; Quiroga, J; Pertuz, A
Abstract: Composite materials are joined in many occasions with adhesive joints due to the condition of the materials, the ease of repair, the loading conditions, the affectation by corrosion and chemical attacks. However, the efficiency of these bonding schemes is related to multiple factors, among them, the length and the width of the adhesion zone and the thickness of the adhesive. In this work, we analyze the factors associated with the surface contact of the substrates. We define a numerical model using the finite element method and study the parameters related to the physical condition, considering optimal results based on the data of the strength provided by the suppliers of adhesives.